2019
DOI: 10.3390/molecules24244443
|View full text |Cite
|
Sign up to set email alerts
|

The Role of c-Met as a Biomarker and Player in Innate and Acquired Resistance in Non-Small-Cell Lung Cancer: Two New Mutations Warrant Further Studies

Abstract: The c-Met receptor is a therapeutically actionable target in non-small-cell lung cancer (NSCLC), with one approved drug and several agents in development. Most suitable biomarkers for patient selection include c-Met amplification and exon-14 skipping. Our retrospective study focused on the frequency of different c-Met aberrations (overexpression, amplification and mutations) in 153 primary, therapy-naïve resection samples and their paired metastases, from Biobank@UZA. Furthermore, we determined the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…Han et al (26) found miR-1 could inhibit gastric cancer cell proliferation and (12). Our results indicated that MET could be a prognostic biomarker for TNBC which was similar to previous studies (28,29).…”
Section: Discussionsupporting
confidence: 90%
“…Han et al (26) found miR-1 could inhibit gastric cancer cell proliferation and (12). Our results indicated that MET could be a prognostic biomarker for TNBC which was similar to previous studies (28,29).…”
Section: Discussionsupporting
confidence: 90%